2023
DOI: 10.1177/16094069221148406
|View full text |Cite
|
Sign up to set email alerts
|

Critical Reflections on Conducting Qualitative Health Research During COVID-19: The Lived Experiences of a Cohort of Postgraduate Students in a South African University

Abstract: COVID-19 ushered in public health guidelines restricting face-to-face contact and movement, and encouraging social distancing, all of which had implications for conducting field-based research during the pandemic. For qualitative researchers, this meant adapting conventional face-to-face methods and resorting to virtual variations of the same in adherence to stipulated COVID-19 health protocols. Virtual qualitative research introduced new concerns and logistical challenges. This paper presents critical reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Another challenge was that nationally scheduled power cuts (loadshedding) negatively influenced participants' Wi-Fi access resulting in long download times. Challenges because of loadshedding have also been reported by various authors who confirmed that the continuous loadshedding in South Africa has a huge impact on healthcare, including the use of mHealth tools (Githaiga et al 2023;Malange 2023;Romski et al 2023).…”
Section: Social Determinants Of Healthmentioning
confidence: 72%
“…Another challenge was that nationally scheduled power cuts (loadshedding) negatively influenced participants' Wi-Fi access resulting in long download times. Challenges because of loadshedding have also been reported by various authors who confirmed that the continuous loadshedding in South Africa has a huge impact on healthcare, including the use of mHealth tools (Githaiga et al 2023;Malange 2023;Romski et al 2023).…”
Section: Social Determinants Of Healthmentioning
confidence: 72%
“… 53 Interestingly, recent developments have looked into the use of technology in shaping qualitative research protocol development, data collection, and analysis phases. 54 …”
Section: Qualitative Researchmentioning
confidence: 99%
“…While we know much about use of conversational face- to-face methods in conducting research on VAW, the use of remote methods to conduct violence research is an emerging area [ 9 ]. At the time when research was conducted there were guidelines on how to conduct clinical trials during lockdown [ 10 , 11 ], but there was limited information on how to conduct qualitative research [ 12 , 13 ]. The lockdown thus required innovation and adaptation of the design and conduct of qualitative research using remote methods [ 14 ].…”
Section: Introductionmentioning
confidence: 99%